The Environmental Factors Associated With Fatigue of Frontline Nurses in the Infection Disease Nursing Unit - Ma, Ming; Adeney, Michael; Long, Hao; He, Baojie (Frontiers in Public Health, 2021)
The workload in the Infection Disease Nursing Unit (IDNU) is increasing dramatically due to COVID-19, and leads to the prevalence of fatigue among the frontline nurses, threatening their health, and safety. The built environment and design could fundamentally affect the fatigue of nurses for a long-term perspective. This article aims to extract the environmental factors of IDNU and explore nurses' perceptions of these factors on the work-related fatigue. It would produce evidences for mitigating the fatigue by environmental interferons. A cross-sectional design was employed by combination of focus group interview and written survey. Environmental factors of IDNU were collected from healthcare design experts (n = 8). Nurses (n = 64) with frontline COVID-19 experiences in IDNU were recruited to assess these factors individually. Four environmental factors were identified as: Nursing Distance (ND), Spatial Crowdness (SC), Natural Ventilation, and Light (NVL), and Spatial Privacy (SP). Among them, ND was considered as the most influential factor on the physical fatigue, while SP was on the psychological fatigue. Generally, these environmental factors were found to be more influential on the physical fatigue than the psychological fatigue. Technical titles were found to be associated with the nurses' perceptions of fatigue by these environmental factors. Nurse assistant and practical nurse were more likely to suffer from the physical fatigue by these factors than senior nurse. The result indicated that environmental factors of IDNU were associated with the nurses' fatigue, particularly on the physical aspect. Environmental interventions of design could be adopted to alleviate the fatigue by these factors such as reducing the ND and improving the spatial privacy. The accurate interventional measures should be applied to fit nurses' conditions due to their technical titles. More attention should be given to the low-ranking nurses, who account for the majority and are much vulnerable to the physical fatigue by environmental factors.